(untitled) - Gordon, Florence S. (New York, 1994)
The book involves students in applying statistical concepts and methods to conduct a variety of statistical projects to study situations of of interest to them; integrates computer graphics software; and presents "real" data in relevant examples and realistic situations to illustrate the concepts
Keywords: Statistics,Statistics; Data processing